Enhancing Market Reach through Branding and Digital Marketing: The Case of Organic Rice in Kediri Regency - Demmy Filsafa Ratna Putra; Novi Dwi Priambodo; Nuansa Bening Cahaya Nurani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze how brand identity and digital marketing capabilities expand market reach and increase the competitiveness of organic rice in Kediri Regency through brand awareness and image. The study uses a mixed-method explanatory sequential design: a survey of 100 consumers was analyzed using SEM-PLS to test the relationships between constructs, followed by in-depth interviews with business actors that were processed in a SWOT analysis. The measurement model meets the criteria of validity and reliability, while the structural model shows that brand identity significantly increases brand awareness, which in turn strengthens image and competitiveness. Digital marketing capabilities have a direct effect on competitiveness as well as an indirect effect through increased brand awareness and image, particularly through the use of social media, marketplaces, and direct-to-consumer channels. The SWOT results emphasize the importance of strengthening the narrative of identity and product origin, standardizing packaging and digital content, ensuring quality and certification, and managing advertising costs and price-packaging structures. It is concluded that the integration of branding and digital marketing strategies is key to expanding the market reach and sustaining the competitiveness of Kediri organic rice